Ivabradine in the Management of COVID-19-related Cardiovascular Complications: A Perspective - Baka, Tomas; Repova, Kristina; Luptak, Ivan; Simko, Fedor (Current Pharmaceutical Design, 2022)
Besides acute respiratory distress syndrome, acute cardiac injury is a major complication in severe coronavirus disease 2019 (COVID-19) and is associated with a poor clinical outcome. Acute cardiac injury with COVID-19 can be of various etiologies, including myocardial ischemia or infarction and myocarditis, and may compromise cardiac function, resulting in acute heart failure or cardiogenic shock. Systemic inflammatory response increases heart rate (HR), which disrupts the myocardial oxygen supply/demand balance and worsens cardiac energy efficiency, thus further deteriorating the cardiac performance of the injured myocardium. In fact, the combination of elevated resting HR and markers of inflammation synergistically predicts adverse cardiovascular prognosis. Thus, targeted HR reduction may potentially be of benefit in cardiovascular pathologies associated with COVID-19. Ivabradine is a drug that selectively reduces HR via If current inhibition in the sinoatrial node without a negative effect on inotropy. Besides selective HR reduction, ivabradine was found to exert various beneficial pleiotropic effects, either HR-dependent or HR-independent, including anti-inflammatory, anti-atherosclerotic, anti-oxidant and antiproliferative actions and the attenuation of endothelial dysfunction and neurohumoral activation. Cardioprotection by ivabradine has already been indicated in cardiovascular pathologies that are prevalent with COVID-19, including myocarditis, acute coronary syndrome, cardiogenic shock or cardiac dysautonomia. Here, we suggest that ivabradine may be beneficial in the management of COVID-19- related cardiovascular complications.
Keywords: cardiac injury